Second language acquisition and acculturation: similarities and differences between immigrants and refugees - Jasemi, Ali; Gottardo, Alexandra (Frontiers in Communication, 2023)
Refugees and immigrants differ in their reasons for migration and their criteria for entry into Canada. This study examined relations among English language and literacy skills, Trauma and psychological distress, and acculturation variables for newcomer Iranian refugees and immigrants in Canada. The refugees scored lower on variables related to socio-economic status and had lower English skills than the immigrant group. English word-reading and vocabulary were related to second language reading comprehension for immigrants, but only word-reading was related for refugees. The experienced trauma was significantly higher among the refugees. However, the trauma was not a significant predictor for any of the English proficiency skills. Acculturation was related to English reading comprehension, and enculturation was negatively associated with English vocabulary and reading comprehension for refugees but not for immigrants. The findings point to similarities and differences between refugees and immigrants. Some remedies and recommendations will be discussed.